DESCRIPTIVE OPINION “BOJA HAVE SKATE” COMMUNITY IN BOJA - Kinasih, Octy Ayu (LANTERN (Journal on English Language, Culture and Literature), 2016)
“Boja Have Skate” is a skateboard community in Boja.  Boja is a district in Semarang.  The discussion of this thesis is about member’s opinion about “Boja Have Skate” community in Boja.  Boja teenagers have experienced the new culture process through skateboard. This research purposes to know about the opinion of “Boja Have Skate” community.  Ten members of “Boja Have Skate” are taken as the respondents.  The analyze and research use theory of social community and the use of cultural product. The result of the research reveals that community of “Boja Have Skate” is formed because they have the same interest and hobby to play skateboard.  At the beginning, the community only has two teenagers who like playing skateboard, they make the other teenagers interested to know and learn about the game.  Boja teenagers get the information about skateboard from internet. The community of “Boja Have Skate” chooses the skateboard because they think that the game is challenging, not mainstream, and interesting to follow.  Skateboard makes the Boja teenagers able to express their existence, get pleasure and stisfy themselves.